2011
DOI: 10.3109/09537104.2011.624211
|View full text |Cite
|
Sign up to set email alerts
|

Which is the best anticoagulant for whole blood aggregometry platelet function testing? Comparison of six anticoagulants and diverse storage conditions

Abstract: Major hindrances of impedance aggregometry are caused by limited storage time and the requirement of ex vivo anticoagulation. Data on the influence of different anticoagulants and storage conditions are rare and incomplete. This study has systematically examined the influence of six different anticoagulants (sodium and lithium heparin, 20 µg/mL and 45 µg/mL r-hirudin, benzylsulfonyl-D-Arg-Pro-4-amidinobenzylamide (BAPA), and citrate) on the results of Adenosine 5'-diphosphate (ADP) and arachidonic acid (AA) in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
46
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(52 citation statements)
references
References 40 publications
6
46
0
Order By: Relevance
“…The results of platelet-function measurements depend on many variables, such as the different assays and cutoff values and the diverse specific and unspecific stimulants used, as well as on preanalytic variables, such as the anticoagulants used, storage time, and temperatures. [35][36][37] Variable prevalence of low-antiplatelet response to acetylsalicylic acid and thienopyridines, ranging between 1% to 45%, have been reported. 36,38 One of the crucial first steps of sample preparation for all platelet function testing, including for the TEG platelet-mapping assay, is ex vivo anticoagulation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The results of platelet-function measurements depend on many variables, such as the different assays and cutoff values and the diverse specific and unspecific stimulants used, as well as on preanalytic variables, such as the anticoagulants used, storage time, and temperatures. [35][36][37] Variable prevalence of low-antiplatelet response to acetylsalicylic acid and thienopyridines, ranging between 1% to 45%, have been reported. 36,38 One of the crucial first steps of sample preparation for all platelet function testing, including for the TEG platelet-mapping assay, is ex vivo anticoagulation.…”
Section: Discussionmentioning
confidence: 99%
“…[35][36][37] Variable prevalence of low-antiplatelet response to acetylsalicylic acid and thienopyridines, ranging between 1% to 45%, have been reported. 36,38 One of the crucial first steps of sample preparation for all platelet function testing, including for the TEG platelet-mapping assay, is ex vivo anticoagulation. Platelets are stabilized in vivo by such mediators as nitric oxide, prostaglandin I2, prostacyclin, and endothelial ADPase to prevent pathologic thrombus formation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Reference values for Lithium Heparin are reported, as values for Sodium Heparin are not available from the manufacturer. Kaiser, et al showed that Sodium Heparin and Lithium Heparin anticoagulated samples give equal results for ADP in the first hour after sample collection [14]. During further storage Sodium Heparin conserved the results better than Lithium Heparin.…”
Section: Multiplate Analysismentioning
confidence: 99%
“…Other studies assessing the use of hirudin with Multiple Electrode Aggregometry (MEA) demonstrated stability in results obtained with hirudin up to 12 hours post sampling [7,8].…”
mentioning
confidence: 99%